DIGITAL TOOLS THAT SUPPORT STUDENT WRITING IN HIGHER EDUCATION (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In the rapidly evolving landscape of Higher Education, digital tools have become essential in supporting student writing development. Writing at the tertiary level requires not only mastery of academic conventions but also critical thinking, creativity, and collaboration. Traditional approaches to teaching writing are increasingly being supplemented and in some cases transformed by digital technologies that offer innovative, accessible, and personalized learning experiences. This article explores the role of digital tools in enhancing student writing skills, with particular emphasis on platforms such as grammar and style checkers (e.g., Grammarly), collaborative writing environments (e.g., Google Docs, Microsoft OneDrive), citation managers (e.g., Zotero, Mendeley), and AI-powered writing assistants. These tools provide students with immediate feedback, foster peer collaboration, and reduce the cognitive load associated with mechanical aspects of writing, allowing greater focus on content development and argumentation. Moreover, the use of digital platforms encourages self-directed learning, supports multilingual learners, and bridges gaps in academic writing proficiency across diverse student populations. However, the integration of such tools is not without challenges, including issues of over-reliance, ethical concerns, and unequal access to technology. By critically examining the affordances and limitations of digital writing support systems, this article highlights their potential to enhance academic success and cultivate transferable communication skills. Ultimately, digital tools, when used strategically and ethically, can empower students to become more confident, independent, and effective writers in higher education and beyond.